2017
DOI: 10.1080/10520295.2017.1341058
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of verdeluz orange G and modified Gallego stains

Abstract: Tumors of the oral cavity include combinations of hard and soft tissues that may be difficult to identify using routine hematoxylin and eosin (H & E) staining. Although combination stains can demonstrate hard and soft tissues, trichrome stains, such as VanGieson and Masson, cannot differentiate dental hard tissues, such as dentin, cementum and osteoid. Modified Gallegos (MGS) and verdeluz orange G-acid fuchsin (VOF) stains can differentiate components of teeth. We used 10 tissue sections of decalcified bone an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The authors confirmed that VOF showed better staining intensity for hard tissues and exhibited good contrast with surrounding connective tissue. [ 15 ] In the present study a natural compound, Kumkum was found to differentiate immature from mature bone. Structures such as canaliculi of osteocytes, resting and reversal lines of bone had a better contrast with increased staining intensity.…”
Section: Discussionmentioning
confidence: 67%
“…The authors confirmed that VOF showed better staining intensity for hard tissues and exhibited good contrast with surrounding connective tissue. [ 15 ] In the present study a natural compound, Kumkum was found to differentiate immature from mature bone. Structures such as canaliculi of osteocytes, resting and reversal lines of bone had a better contrast with increased staining intensity.…”
Section: Discussionmentioning
confidence: 67%
“…When stained with Modified Gallego's stain, these components were stained with different colours as follows (Sandhya et al, 2014). It stains dentin in dark blue color as shown in figure 4, the dentinal tubules were observed as dark blue striations as shown in figure 4 while the coronal dentin is stained in light blue color as shown in figure 5 and interglobular dentin looks violet blue after staining with modified Gallego's stain as shown in figure 6 (Kunche et al, 2017). This staining procedure is technique sensitive and the intensity of the colour in the stained sections decreases as the time duration increases and becomes difficult to differentiate between the dentin at different parts (Comparison of Verdeluz Orange G and Modified Gallego Stains, 2017).…”
Section: Discussionmentioning
confidence: 98%